2016
DOI: 10.1186/s12936-016-1417-0
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal exposure to Plasmodium falciparum increases frequency and shortens time from birth to first clinical malaria episodes during the first two years of life: prospective birth cohort study

Abstract: BackgroundPrenatal exposure to Plasmodium falciparum affects development of protective immunity and susceptibility to subsequent natural challenges with similar parasite antigens. However, the nature of these effects has not been fully elucidated. The aim of this study was to determine the effect of prenatal exposure to P. falciparum on susceptibility to natural malaria infection, with a focus on median time from birth to first clinical malaria episode and frequency of clinical malaria episodes in the first 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 30 publications
2
40
1
Order By: Relevance
“…An additional study that rigorously controlled for environmental risk factors confirmed the association between PM and risk of malaria infection . Further studies from Tanzania and Uganda described an association between PM and risk of malaria infection, as well as a study from Mozambique that found that infants born to mothers with PM had a higher risk of first time clinical malaria as well as overall risk of clinical malaria compared to those born to uninfected women . Interestingly, one recent study also found that infants were specifically at increased risk of parasites that carried a matching glurp allele as those that infected their mothers’ placentas .…”
Section: Maternal Malaria Predicts An Increased Risk Of Malaria Durinmentioning
confidence: 82%
“…An additional study that rigorously controlled for environmental risk factors confirmed the association between PM and risk of malaria infection . Further studies from Tanzania and Uganda described an association between PM and risk of malaria infection, as well as a study from Mozambique that found that infants born to mothers with PM had a higher risk of first time clinical malaria as well as overall risk of clinical malaria compared to those born to uninfected women . Interestingly, one recent study also found that infants were specifically at increased risk of parasites that carried a matching glurp allele as those that infected their mothers’ placentas .…”
Section: Maternal Malaria Predicts An Increased Risk Of Malaria Durinmentioning
confidence: 82%
“…4 While the obstetric complications of PM have been studied extensively, it remains unclear whether prenatal exposure to malaria has a lasting detrimental impact on the infant. Notably, several observational studies have reported that infants born to women with PM are themselves at higher risk of malaria during early life, [7][8][9][10][11][12][13][14] and may even have increased vulnerability to non-malarial febrile illnesses. 15 In this review, we summarize recent advances in our understanding of how the fetal immune system responds to malaria antigens encountered as a result of P. falciparum infection during pregnancy.…”
mentioning
confidence: 99%
“…Several prior studies have reported associations between active PM de ned as detection of parasites in placental blood or tissue and an increased risk of malaria during infancy [9][10][11][24][25][26]. Active PM detected by microscopy was associated with a higher risk of malaria infection in Ugandan infants [24], an increased rate of rst parasitemia in Beninese infants [11], and a higher risk of rst episode of malaria in Gabonese infants [25].…”
Section: Discussionmentioning
confidence: 96%